(3YLGFH Ydhe GdbQBf (B/s - (3GHf GdLhRj s; (3YGThQ(B,(3YHO GdaJGMs ((3GdLRGFQ (B:s (3GdRgQGA ddEYdGe GdYQHj (B;(3OjhGf GdeWHhYGJ GdLGeYjI ,s, 1988)
(3YHQ gPG GdcJGH jUMHc GHf GdLhRj aj QMdI eeJYI agPG HGH aj aVGFd GdbQBf hPGc HGH aj Cf GdbQBf ZjQ eNdhb (B,(3hHGH aj fRhd GdbQBf Ydi SHYI CMQa hHGH aj aj cJGHg GdeUMa h gLGFg hHGH aj YOO ShQGdbQBf hBjGJg hcdeGJg h MQhag hfbWI hHGH aj BOGH Gdhba h GdGHJOGA Edi ZjQ Pdc ef GdeHGMK GdObjbI GdJj JOYhc Edi bQGAJgG (B.s
Keywords: (3GdbQBfs; (3YLGFH s; (3Ydhe s